How organizational culture shapes women's leadership experiences - Karen Longman; Jessica Daniels; Debbie Lamm Bray; Wendy Liddell (Administrative Sciences, 2018)
This article presents the findings of a grounded theory study that examined the role of organizational culture and organizational fit in the leadership aspirations and experiences of 16 women working in faith-based colleges and universities in the U.S. Specifically, the researchers sought to understand what aspects of organizational culture at the home institutions of these participants influenced their employment experiences, including their considerations and decisions related to aspiring to and/or advancing into leadership. Analysis of the interview data indicated that the participants clustered into four subgroups: (1) participants who did not perceive that gender issues in the culture influenced their work or roles within the institution; (2) participants who reported that they did not perceive gender issues to be an institutional problem; however, they cited examples of problematic systems and cultures; (3) participants who identified gender inequalities at their institution, but indicated that such problems impacted them only minimally, if at all; and (4) participants who offered explicit criticism regarding the gendered dynamics evident in the culture in their institutions and in Christian higher education more broadly. Influences on leadership aspirations or experiences were identified as either being 'push' (i.e., propelling the participant away from the organization and thus diminishing aspirations or willingness to move into or remain in leadership) or 'pull' (i.e., drawing the participant into further engagement with the organization, thus increasing the desire to become or remain a leader in that context), with particular attention to the context of faith-based higher education. The article concludes with a brief discussion of implications for practice for individuals and postsecondary institutions.
Keywords: 350; organizational culture; institutional leadership; women and leadership; leadership aspirations